Comparison of behaviorally inhibited and typically developing children’s play behaviors in the preschool classroom - Druskin, Lindsay R.; Novick, Danielle R.; Smith, Kelly A.; Chronis-Tuscano, Andrea; Wagner, Nicholas J.; Pham, Stephanie; Fleece, Hailey M.; Danko, Christina M.; Rubin, Kenneth H. (Frontiers in Psychology, 2023)
Behavioral inhibition (BI) is a temperamental trait characterized by a bias to respond with patterns of fearful or anxious behavior when faced with unfamiliar situations, objects, or people. It has been suggested that children who are inhibited may experience early peer difficulties. However, researchers have yet to systematically compare BI versus typically developing children’s observed asocial and social behavior in familiar, naturalistic settings. We compared the in-school behaviors of 130 (M = 54 months, 52% female) highly inhibited preschoolers (identified using the parent-reported Behavioral Inhibition Questionnaire) to 145 (M = 53 months, 52% female) typically developing preschoolers. Both samples were observed on at least two different days for approximately 60 minutes. Observers used the Play Observation Scale to code children’s behavior in 10-second blocks during free play. Teachers completed two measures of children’s behavior in the classroom. Regression models with robust standard errors controlling for child sex, age, and weekly hours in school revealed that preschoolers identified as BI engaged in significantly more observed reticent and solitary behavior, and less social play and teacher interaction than the typically developing sample. Children with BI also initiated social interaction with their peers and teachers less often than their counterparts who were not inhibited. Teachers reported that children identified as BI were more asocial and less prosocial than their non-BI counterparts. Significantly, the findings indicated that inhibited children displayed more solitude in the context of familiar peers. Previous observational studies have indicated behavioral differences between BI and unfamiliar typical age-mates in novel laboratory settings. Children identified as BI did not receive fewer bids for social interaction than their typically developing peers, thereby suggesting that children who are inhibited have difficulty capitalizing on opportunities to engage in social interaction with familiar peers. These findings highlight the need for early intervention for children with BI to promote social engagement, given that the frequent expression of solitude in preschool has predicted such negative outcomes as peer rejection, negative self-regard, and anxiety during the elementary and middle school years.